2017
DOI: 10.1371/journal.pone.0181327
|View full text |Cite
|
Sign up to set email alerts
|

The distracted mind on the wheel: Overall propensity to mind wandering is associated with road crash responsibility

Abstract: The role of distractions on attentional lapses that place road users in higher risk of crash remains poorly understood. We aimed to assess the respective impact of (i) mind wandering trait (propensity to mind wander in the everyday life as measured with a set of 4 questions on the proportion of time spent mind wandering in 4 different situations) and (ii) mind wandering state (disturbing thoughts just before the crash) on road crash risk using a comparison between responsible and non-responsible drivers. 954 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…For instance, perhaps while driving to work, you catch yourself thinking about the groceries you need to get later in the day, or the upcoming fishing trip that you have planned for the weekend. Of course, failing to maintain your attention on the road can be dangerous, increasing the likelihood you will make a potentially disastrous mistake (Gil-Jardiné et al, 2017;Yanko & Spalek, 2014). Alas, mind wandering tends to get a bad rap for its often-negative consequences on task performance (see Mooneyham & Schooler, 2013 for a review); indeed, some even refer to it as a curse (Hasenkamp, 2013)!…”
mentioning
confidence: 99%
“…For instance, perhaps while driving to work, you catch yourself thinking about the groceries you need to get later in the day, or the upcoming fishing trip that you have planned for the weekend. Of course, failing to maintain your attention on the road can be dangerous, increasing the likelihood you will make a potentially disastrous mistake (Gil-Jardiné et al, 2017;Yanko & Spalek, 2014). Alas, mind wandering tends to get a bad rap for its often-negative consequences on task performance (see Mooneyham & Schooler, 2013 for a review); indeed, some even refer to it as a curse (Hasenkamp, 2013)!…”
mentioning
confidence: 99%
“…In other studies, research led by Gil-Jardiné and Mason identified significant positive correlations between trait mind wandering and both distracted thoughts while driving (Gil-Jardiné et al, 2017) and having stimulus-independent thoughts while performing a habitual routine (Mason et al, 2007). Although both measured TUT at the state level, each group used items from the daydreaming frequency scale (Giambra, 1993) to determine trait mind wandering.…”
Section: The Assumption That Measures Of Mind Wandering or Daydreaminmentioning
confidence: 96%
“…45 The vehicle could instead be deemed defective for failing to timely warn the user of the need to resume control under critical conditions, and should take into account the propensity of human beings in getting distracted, as well as the average reaction time required to understand what is happening and acquiring control of the vehicle, by applying a consumer-expectation test, leading the trier to conclude that it was unreasonable to require a human being, not directly involved in the driving task -eventually even intended to supervise the vehicle -, to maintain a sufficient level of attention to abruptly intervene, and timely avoid collision. Studies show how human users have a propensity to distract themselves when driving, see Gil-Jardiné et al (2017).…”
Section: Cont: Apportioning Liability Between User and Producermentioning
confidence: 99%